The cactus-specialist bees of the genus brachyglossula Hedicke (Hymenoptera: Colletidae): Notes on host associations and description of a new species - Roig Alsina, Arturo Hernan (2008)
The pollen-collecting behavior of three species of the South American Andean bee genus Brachyglossula is reported. Species studied are B. martinezi Trucco Alemn, B. communis Trucco Alemn, and B. ancasti Roig Alsina and Schlumpberger, new species. The new species, which is comparatively described and illustrated, inhabits the isolated mountain range of Sierra de Ancasti, in the province of Catamarca, Argentina. Observation of the bees in the field, and pollen counts from scopal loads strongly support specialization of these bees on the Cactaceae. Members of both major cactus subfamilies, the Opuntioideae and the Cactoideae, are frequently visited and represented in the pollen loads.